ECOLOGICAL AND ECONOMIC EFFECTS OF REGENERATION OF WASTE OILS BY THE METHOD OF THEIR SETTLING - Карпенко, Сергій Володимировіч; Пузік, Сергій Олексійович; Вапнічний, Артур Борисович (Problems of Friction and Wear, 2021)
The ecological and economic problem from the use of substandard oil products is considered and it is found that the defense of oils from particles of pollution is the first and obligatory operation of the regeneration process. Savings in petroleum products have become relevant due to the increase in their use, as well as environmental problems associated with environmental pollution. The dynamics of pollution particles during settling and the mass of the temperature regime are analytically investigated. The rate of deposition of contaminant particles has been found to be greater the larger the radius and density and the lower the viscosity of the oil. Given that the viscosity of the oil decreases with increasing temperature, it is advisable to defend at elevated temperatures. The most effective contamination is released from the oil by means of a continuous gravity cleaner, the deposition of contamination particles in such a device is possible provided that the residence time of the oil in the cleaner is greater than or equal to the deposition time of the contamination. It is proved that the productivity of the purifier is proportional to the area of ​​deposition and does not depend on the height of the oil level in it. This pattern is called the condition of the cleaner. Schemes of connection of the gravity cleaner in technological lines of regeneration of the fulfilled oils are offered.